Secularism or Democracy? Associational Governance of Religious Diversity - Bader, Veit (Amsterdam University Press, 2007)
Established institutions and policies of dealing with religious diversity in liberal democratic states are increasingly under pressure. Practical politics and political theory is caught in a trap between a fully secularized state (strict separation of state and politics from completely privatized religions based on an idealized version of American denominationalism or French republicanism) and neo-corporatist or 'pillarized' regimes of selective cooperation between states and organized religions. The book offers an original, comprehensive conceptual, theoretical and practical approach to problems of governance of religious diversity from a multi-disciplinary perspective combining moral and political philosophy, constitutional law, history, sociology and anthropology of religions and comparative institutionalism. Proposals of associative democracy - a moderately libertarian, flexible version of democratic institutional pluralism - are introduced and scrutinized whether they can serve as as plausible third way overcoming the inherent deficiencies of the predominant models in theory and practice.